Struktura psihološkega pregleda za oceno delazmožnosti - Molan, Marija (Psihološka obzorja (Ljubljana), 2000)
Results of psychological test of 46 workers were analysed. All were men with technical high-school education and all worked as operators. Psychological tests and questionnaires for assessment of basic and specific abilities, personality characteristics, level of manifested unavailability and self-estimated fitness for duty were administered. The analysis of results proofs the selection of psycho-diagnostic procedures to be rational and economic. According to the results of factor analysis, all basic mental functions were assessed, which had previously been identified as relevant for job performance by job analysis. According to the results of factor analysis, the administered tests are adequate and their factor structure is clear.
Keywords: delazmožnost; psihološki pregledi; sposobnosti; osebnost; personality